2021
DOI: 10.1108/ecam-07-2020-0521
|View full text |Cite
|
Sign up to set email alerts
|

Research on the rework risk core tasks in prefabricated construction in China

Abstract: PurposeThe purpose of this paper is to assess the process of prefabricated construction (PC) and analyze the impacts of rework risk to identify the core tasks for which the rework risk has severe impacts.Design/methodology/approachThe methods consist of a literature review, expert interviews, a questionnaire survey and a rework risk function. The expert interviews and questionnaire survey were administered to experts in the entire process of PC from the dimensions of rework frequency, rework cost and rework ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Modeling Process 3.1.1. Factors Influencing SCR An extensive analysis of existing works on SCR and precursor risks in construction contexts [44][45][46][47][48][49][50][51][52] provided the basis for identifying relevant factors. Text mining techniques were applied to scan these articles in order to derive an initial set of keywords.…”
Section: Methodsmentioning
confidence: 99%
“…Modeling Process 3.1.1. Factors Influencing SCR An extensive analysis of existing works on SCR and precursor risks in construction contexts [44][45][46][47][48][49][50][51][52] provided the basis for identifying relevant factors. Text mining techniques were applied to scan these articles in order to derive an initial set of keywords.…”
Section: Methodsmentioning
confidence: 99%
“…As supported by Lee and Kim (2017), while carrying out a Failure Mode and Effects Analysis, half of the risk factors are workforce failures, and the cost risk increases alarmingly in the design phase. Similarly, rework risks analyzed in the Chinese prefabrication sector add to the industry's inefficiency (Shen et al, 2021). Prefabrication safety risks need attention (Jeong et al, 2021;Liu Q. et al, 2019).…”
Section: Research Backgroundmentioning
confidence: 99%
“…(2017) and Wuni and Shen (2020a) that site-fit reworks are critical technical risks during the OA stage of MiC projects. Shen et al. (2021) also concluded that onsite reworks generate significant adverse implications on the cost, time and quality of MiC projects in China.…”
Section: Literature Reviewmentioning
confidence: 99%